Physiological, physical and anthropometric parameters in padel: A systematic review - Martín-Miguel, I.; Escudero-Tena, A.; Sánchez-Alcaraz, B. J.; Courel-Ibáñez, J.; Muñoz, D. (International Journal of Sports Science and Coaching, 2025)
This study aimed to carry out a systematic review of existing research on physiological, physical and anthropometric parameters in padel. After searching through PubMed, Scopus, Google Scholar, and Web of Science, 33 articles were analyzed, covering physiological, physical, and anthropometric parameters. Physiologically, heart rate varies by sex and play level; men amateurs show a lower maximum heart rate compared to semi-professionals and professionals (154.75 vs 169.72 vs 188.6 beats per minute). Women players maintain consistent maximum heart rate across levels (~178 beats per minute). Lactate levels during competition indicate effort within the aerobic transition zone, peaking at 2.40 millimole per liter in women and 3.38 millimole per liter in men. Regarding maximal oxygen consumption, padel players exhibit levels around 76.3%, increasing to 95.1% during peak exertion. Biochemical and hematological parameters vary by sex, with men players typically having higher basal levels, while competition reduces certain elements like copper and zinc. Physically, men players exhibit superior jump height, strength, and maximum speeds around 2.09 kilometers per hour, with significant lateral movements. The average distance covered per match is 3000 meters, with higher-level players traveling less. Anthropometrically, men players are taller with a mesomorphic-endomorphic profile, while women players have an endomorphic-mesomorphic somatotype. The study highlights the need for tailored training based on specific player characteristics and calls for further research to better individualize physical preparation in padel.